The Synergity of Cottage Managers in Improving Mental Health through the Discipline of Student Prayer in Congregations SMK Al-Kirom - Siti Roudhotul Jannah; Jaenal Arifin; Izroni Izroni; Agung Bayu Saputra (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
The existence of synergy between the boarding school administrators and the foundation's school teachers is very necessary in order to form a generation of devout Muslims. Administrators and teachers are expected to synergize better by having the same goal, namely developing, nurturing, directing and forming students to carry out religious obligations such as congregational prayers. The aim of conducting this research is to describe and analyze the understanding, implementation and synergy of administrators and teachers in improving the discipline of congregational prayer at Al-Kirom Vocational School students. This research is field research (field research) carried out at Al-Kirom Vocational School is related to the synergy of administrators and teachers in improving student congregational prayer discipline. Researchers in collecting the data needed as a source of information, use observation, interview and documentation techniques. From the data obtained, it is then collected and processed so that a conclusion can be drawn. Based on the research results, it can be concluded that the administrators of the Al-Kirom Islamic Boarding School, in their efforts to improve the discipline of congregational prayer for Al-Kirom Vocational School students, have carried out various efforts, one of which is by collaborating with teachers. The synergy that exists between administrators and teachers is not solely for the benefit of the Islamic boarding school, but is for the common interest and especially the interests of the students. With the activities running within the school and the synergy with the boarding school administrators, it is hoped that the discipline of congregational prayer at Al-Kirom Vocational School students will be even better. Keywords: Mental Health, Congregational Prayer, Cottage Managers